The mediated innovation model: A framework for researching media influence in language change - Dave Sayers (Journal of Sociolinguistics, 2014)
Linguistic innovations that arise contemporaneously in highly distant locations, such as quotative 'be like', have been termed 'global linguistic variants'. This is not necessarily to suggest fully global usage, but to invoke more general themes of globalisation vis-à-vis space and time. This research area has grown steadily in the last twenty years, and by asserting a role for mass media, researchers have departed intrepidly from sociolinguistic convention. Yet they have largely relied on quite conventional sociolinguistic methodologies, only inferring media influence post hoc. This methodological conservatism has been overcome recently, but uncertainty remains about the overall shape of the new epistemological landscape. In this paper I review existing research on global variants, and propose an epistemological model for researching media influence in language change: the mediated innovation model. I also analyse the way arguments are constructed in existing research, including the use of rhetorical devices to plug empirical gaps – a worthy sociolinguistic topic in its own right.